Pengembangan Sistem Manajemen Pesanan dan Pengiriman Barang pada Perusahaan Perdagangan berbasis Web (Studi Kasus: PT Arista Semesta Alam) - Emma Wahyu Sulistianingrum; Denny Sagita Rusdianto; Randy Cahya Wihandika (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The constraints experienced by PT Arista Semesta Alam are currently related to business processes that are still conventional, resulting in losses to the company in terms of time and staff. In addition, it also affects the low growth of consumers, it is feared that this could disrupt business continuity in the future. This conventional business process includes the ordering process, delivery of goods, and delivery evaluation. The Order and Delivery Management System is the right solution because this system facilitates companies to make changes to business processes towards digital so that they can save time and employee energy. This system is based on a website so that it can be accessed by the wider community and is expected to help introduce products to the public so that it can increase consumer growth. The order management system and delivery of goods was developed using the waterfall method which consists of the stages of needs analysis, design, implementation, and testing. The requirements analysis stage obtains the required system requirements. The design phase contains the design of the sequence diagram, the design of the class diagram, the design of the database, the design of the algorithm, and the design of the interface. The implementation of the system uses the Slim 3 framework as a back-end supporter and the AngularJS framework as a front-end supporter. Functional testing is carried out by unit testing, integration testing, and validation testing which results in passed status and 100% valid status. Non-functional testing is carried out with a compatibility testing approach which results in system compatibility in five different browser types.